Skimming and Scanning Techniques in Teaching Students’ Reading Comprehension - Nurhayah, Ananda Shafa; Dewi, Puspa; Ngafif, Abdul (Scripta : English Department Journal, 2025)
This study aims to examine the effectiveness of using skimming and scanning techniques in teaching students’ reading comprehension of descriptive texts. The study employed a quantitative method through a pre-experimental design involving a one-group pre-test and post-test. A total of 31 students from the eleventh grade of the Teknik Sepeda Motor department at SMK Ma’arif NU 1 Bener. This data collection was carried out using a reading comprehension test. The results from the pre-test revealed a mean score of 50.32, while the post-test showed a mean score of 69.03. The data analysis involved descriptive statistics, a normality test, and hypothesis testing using SPSS version 25. The analytical findings demonstrated the effectiveness of skimming and scanning strategies in teaching students to comprehend what they read. Following these techniques, there were significant variations between the pre-test and post-test scores, as indicated by the paired sample t-test’s significance value of 0.000 (<0.05). Therefore, the alternative hypothesis (Ha) was accepted, and the null hypothesis (Ho) was rejected.